The impact of the word meaning strategy on reading comprehension among second- grade intermediate students - Basem Turki, Hadeel; Ismail Khalil, Ammar (Al-Adab Journal, 2021)
The current research aims to know "the effect of the strategy of meaning of word on reading comprehension of second-grade intermpediate students. The two researchers have followed experimental method and experimental design of partial control . The two researchers have randomly chosen the sample consisting of 60 , with 30 student for the experimental group and 30 students for the control group. The two researchers statistically included the students of the two research groups using the t-test and the chi-square in the variables (chronological age calculated in months, the academic achievement of parents, and the Arabic language scores for the previous academic year (2018- 2019), and (Raven’s test of intelligence). After analyzing the results of the students ’answers and processing them statistically using appropriate statistical means, the following emerged: The experimental group students who studied the reading material according to the meaning of the word strategy outperformed the control group students who studied the same subject in the traditional way.